Learning TypeScript 2.x : Develop and maintain captivating web applications with ease, 2nd Edition. - Jansen, Remo H. (Birmingham : Packt Publishing, 2018)
TypeScript is an open source and cross-platform statically typed superset of JavaScript that compiles to plain JavaScript and runs in any browser or host. This book is a step-by-step guide that will take you through the use and benefits of TypeScript with the help of practical examples.
Callbacks and higher-order functionsArrow functions; Callback hell; Promises; Covariant checking in callback parameters; Generators; Asynchronous functions -- async and await; Asynchronous generators; Asynchronous iteration (for await ... of); Delegating to another generator (yield*); Summary; Chapter 4: Object-Oriented Programming with TypeScript; Classes; Strict property initialization; Inheritance; Depth of the inheritance tree (DIT); Access modifiers; The public access modifier; The private access modifier; The protected access modifier; Parameter properties; Class expressions.
Print version record.
Static members.
Added to collection customer.56279.3
Keywords: Scripting languages; Computer programming -- software development; Web programming; Programming & scripting languages: general; Computers -- Software Development & Engineering -- Tools; Computers -- Web -- Web Programming; Computers -- Programming Languages -- JavaScript; TypeScript